Textual Erasures of Religion: The Power of Books to Redefine Yoga and Mindfulness Meditation as Secular Wellness Practices in North American Public Schools - Brown, Candy (Mémoires du livre / Studies in Book Culture, 2015)
This essay argues that books, broadly defined to include print and internet publications, played a crucial role in the cultural mainstreaming, including adoption by public schools, of non-Christian religious practices such as yoga and meditation. Promotional books, tactically and ironically, played on the textual bias of Christianity, and especially Protestantism, to re-brand practices borrowed from religious traditions such as Hinduism and Buddhism, as scientific techniques for exercise and stress-reduction, thereby reintegrating religion into public education. The essay begins with a brief history of religion in U.S. and Canadian public education, explains the textual bias of North American assumptions about religion, and analyzes how twentieth-century promoters of practice-centered religions tactically wielded books to increase public acceptance of non-Christian religious practices. The essay focuses on two twenty-first-century examples of religion-based, textually mediated public-school curricula: the Sonima Foundation’s Health and Wellness program of Ashtanga yoga and The Hawn Foundation’s MindUP program of mindfulness meditation.